KOMUNIKASI DAKWAH KH. MOCH. IMAM CHAMBALI DALAM TAYANGAN “PADHANGE ATI” JTV SURABAYA 2015 - Noor Rahmah (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2016)
Da'wah is very dependent on communication. Submission of da'wah needs the existence of forms, processes and communication techniques for the success of these activities. The event